Assessment of the changes in the structure of mangroves based on stand age in Bang La, Hai Phong, Vietnam - Pham, Quang Van; Nguyen, Linh Manh; Vu, Hung Manh (Vietnam Journal of Marine Science and Technology, 2023)
The mangrove forest area in Bang La (Hai Phong) is 370 ha, and tree density is 5,885 individuals/ha, distributed along the upper bank of the Van Uc River with high tidal flats. Detected 20 species of mangrove plants belonging to 19 genera, 16 families, and two divisions. The survey results show that the Bang La mangrove forest ecosystem has three forest types, the forest community is older than 15 years old, the forest community is from 10 to 15 years old, and the forest community is less than 10 years old. Kandelia obovata, Sonneratia caseolaris, and Rhizophora stylosa, is the dominant plant species. In each forest biome of different ages, there are different dominant species. The general composition formula for the study area is 47.2 Ko + 46.9 Sc + 1.8 Ks + 2.1 Ai + 2.0 Ac. The paper results showed that the more than ten years mangrove community is a stable forest biome. Mangroves from 10 years old should be planned with different species to increase the diversity in species structure and enhance the ability to stabilize the community and withstand changes in coastal habitats.